Synthesis and characterization of organic-inorganic membranes - Romaniuk, H. V.; Koval, Z. M.; Demchyna, O. I.; Yevchuk, I. Yu. (Видавництво Львівської політехніки, 2012)
Organic-inorganic membranes were synthesized via photoinitiated polymerization of acrylonitrile, acrylamide and 3-sulphopropylacrylate potassiums altin the presence of sol-gel system ( tetraethoxysilane :ethanol :water). Kinetic parameters of the process of polymerization were determined depending on the amount of sol -gel system added into polymerizing mixture. Water uptake ofobtained materials was found to increase with increasing of sol-gel system content.